Socio Economic Conditions, Schemes Evaluation and Technological Appraisal of Fisherman (A Case Study in Therespuram Village of Tuticorin District, Tamil Nadu) - Paramasivam P (PT FORMOSA CENDEKIA GLOBAL, 2023)
Techniques for catching fish include hand gathering, spearing, netting, angling and trapping. The term fishing may be applied to catching other aquatic animals such as molluscs, cephalopods, crustaceans, and echinoderms. The term is not normally applied to catching farmed fish, or to aquatic mammals, such as whales, where the term whaling is more appropriate. The English rules Thoothukkudi, which was a part of Thirunelveli district, till India’s independence. Tuticorin district is in southern Tamil Nadu, in Gulf of Mannar region, which is situated between India and Srilanka. Tuticorin district names 23 fishing village, with population close to 70,000. Therespurm is one of the village in Tuticorin. It is 9km away from Tuticorin Harbour. Totally around 5,600 fishermen family are living here. 48 wards are there. Also they are using GPS and new Technologies for fishing. Hence the study focusing on socio – economic conditions, schemes evaluation and technological appraisal of fisherman in therrespuram village of Tuticorin.